2012
DOI: 10.1111/j.1600-6143.2012.04220.x
|View full text |Cite
|
Sign up to set email alerts
|

Interim Results of a National Test of the Rapid Assessment of Hospital Procurement Barriers in Donation (RAPiD)

Abstract: Organ donation remains a major public health challenge with over 114 000 people on the waitlist in the United States. Among other factors, extant research highlights the need to improve the identification and timely referral of potential donors by hospital health-care providers (HCPs) to organ procurement organizations (OPOs). We implemented a national test of the Rapid Assessment of hospital Procurement barriers in Donation (RAPiD) to identify assets and barriers to the organ donation and patient referral pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…As a result of their proximity to patients and their relatives, nurses are seen as a key element in raising awareness about donation, and their personal attitudes play a vital role in improving attitudes among society as a whole (Sque et al , ; Mills & Koulouglioti, ; Jawoniyi & Gormley, ). Furthermore, nurses frequently think more about donation than physicians (Traino et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of their proximity to patients and their relatives, nurses are seen as a key element in raising awareness about donation, and their personal attitudes play a vital role in improving attitudes among society as a whole (Sque et al , ; Mills & Koulouglioti, ; Jawoniyi & Gormley, ). Furthermore, nurses frequently think more about donation than physicians (Traino et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Another barrier to donation is the relationship between the staffs of receiving hospitals and the OPO in each region. One study of this relationship concluded that only a small minority of hospital employees viewed OPO staff as part of their team and that improvement in this relationship was needed …”
Section: Supply Demand and The Current Systemmentioning
confidence: 99%
“…The consequential knowledge gap in organ donation practices in non-ICU physicians leads to a loss of potential organ donors (3,4). Organ donation expertise tends to be focused within the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…We tried to limit this bias by interviewing the physicians in the days or weeks following the inclusion. 4 In the other cases a reason for not discussing tissue donation was given (n = 20) or no reason was given (n = 8). Most of our patients would fall within the donation after circulatory death group, and only a minority in donation after brain death.…”
Section: Discussionmentioning
confidence: 99%